Pisemna autonarracja w badaniu różnic indywidualnych w glottodydaktyce - Smuk, Maciej (Neofilolog, 2017)
In general terms, this article presents the practical aspects of narrative forms in research on the process of foreign language learning and teaching. In detail, its purpose is to describe the written auto-narration inquiry concerning the impact of individual factors (savoir-être) in the course of language learning. The article contains a description of the object, the purpose as well as the opinions and feelings of the respondents on the practical implementation of their auto-narrative inquiries.